Kelin (The Daughter-in-Law) - Tursunov, Ermek (Kazakhstan : Kazakhfilm, 2009)
Set in a pre-modern mountain setting, this film is without dialogue. A girl is married off by her father to the wealthiest young man in the vicinity, Baktashy. However, she is in love with Mergen. Before she is taken by Baktashy to his family yurt, Mergen cuts a mark on her arm: a blood oath that he will remain her true love.
Keywords: Fiction films